New Trends in Medical and Service Robots Human Centered Analysis, Control and Design - Wenger, Philippe; Chevallereau, Christine; Pisla, Doina; Bleuler, Hannes; Rodić, Aleksandar (Mechanisms and Machine Science, 2016)
Medical and service robotics integrates several disciplines and technologies such as mechanisms, mechatronics, biomechanics, humanoid robotics, exoskeletons, and anthropomorphic hands. This book presents the most recent advances in medical and service robotics, with a stress on human aspects. It collects the selected peer-reviewed papers of the Fourth International Workshop on Medical and Service Robots, held in Nantes, France in 2015, covering topics on: exoskeletons, anthropomorphic hands, therapeutic robots and rehabilitation, cognitive robots, humanoid and service robots, assistive robots and elderly assistance, surgical robots, human-robot interfaces, BMI and BCI, haptic devices and design for medical and assistive robotics. This book offers a valuable addition to existing literature.